2023
DOI: 10.1186/s12894-023-01283-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of outcomes between dusting and fragmentation in retrograde intrarenal surgery

Abstract: Objectives Comparing stone-free rates and associated outcome measures between two surgical modalities of lithotripsy fragmentation and removal or spontaneous passage of dust during retrograde intrarenal surgery (RIRS). Methods In March 2023, we conducted a literature search in several widely used databases worldwide, including PubMed, Embase, and Google Scholar. We only considered English articles and excluded pediatric patients. Reviews and protoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…‘Basketing’ and ‘dusting’ have emerged as the two main strategies for f-URSL [ 6 ], but it is unclear which strategy is superior. A recent meta-analysis concluded that the basketing strategy led to significantly higher stone-free rate and lower retreatment rate (p=0.01 and p=0.001, respectively), while the dusting group had significantly shorter operative time (p=0.004) [ 7 ]. Three advantages of performing stone extractions compared with dusting are that all stone fragments can be completely extracted, that stone component analysis can be performed, and the lower total laser energy and thermal damage to the urothelium compared with dusting [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…‘Basketing’ and ‘dusting’ have emerged as the two main strategies for f-URSL [ 6 ], but it is unclear which strategy is superior. A recent meta-analysis concluded that the basketing strategy led to significantly higher stone-free rate and lower retreatment rate (p=0.01 and p=0.001, respectively), while the dusting group had significantly shorter operative time (p=0.004) [ 7 ]. Three advantages of performing stone extractions compared with dusting are that all stone fragments can be completely extracted, that stone component analysis can be performed, and the lower total laser energy and thermal damage to the urothelium compared with dusting [ 8 ].…”
Section: Introductionmentioning
confidence: 99%